Daniel Todd Patterson papers - Patterson, Daniel Todd, 1786-1839.
Correspondence, journals, notebooks, reports, list of officers, wills, photographs, portraits, and printed matter relating to Patterson's duties as fleet captain of the flagship U.S. Frigate Constitution and as commander of the Mediterranean Squadron. Includes material on piracy in the Mediterranean region and the squadron's diplomatic and strategic missions there. Also includes orders (1826 October 13) prescribing funeral honors for former presidents John Adams and Thomas Jefferson. Correspondents include William W. Bleecker, Landon N. Carter, William M. Crane, Robert E. Griffin, Charles H. Jackson, John H. Jarvis, Edward Livingston, George Minor, Charles Morris, Joseph J. Nicholson, John B. Nicolson, David Offley, Hiram Paulding, Matthew C. Perry, Richard S. Pinckney, David Porter, Joseph Pulis, George C. Read, John Rodgers, Samuel L. Southard, and Richard Thomas.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Adams, John, -- 1735-1826.; Bleecker, William W. -- Correspondence; Carter, Landon N., -- -1847 -- Correspondence; Crane, William Montgomery, -- 1784-1846 -- Correspondence; Griffin, Robert E., -- active 1802 -- Correspondence; Jackson, Charles H., -- -1878 -- Correspondence; Jarvis, John H. -- Correspondence; Jefferson, Thomas, -- 1743-1826.; Livingston, Edward, -- 1764-1836 -- Correspondence; Minor, George -- Correspondence; Morris, Charles, -- 1784-1856 -- Correspondence; Nicholson, Joseph J., -- -1838 -- Correspondence; Nicolson, John B., -- 1783-1846 -- Correspondence; Offley, David, -- -1838 -- Correspondence; Paulding, Hiram, -- 1797-1878 -- Correspondence; Perry, Matthew Calbraith, -- 1794-1858 -- Correspondence; Pinckney, Richard S., -- -1854 -- Correspondence; Porter, David, -- 1780-1843 -- Correspondence; Pulis, Joseph -- Correspondence; Read, George C. -- 1787-1862 -- Correspondence; Rodgers, John, -- 1773-1838 -- Correspondence; Southard, Samuel L. -- 1787-1842 -- Correspondence; Thomas, Richard, -- 1779-1858 -- Correspondence; Constitution (Frigate); United States -- Navy -- History; United States. -- Navy. -- Mediterranean Squadron; Diplomatic and consular service, American -- Mediterranean region; Naval ceremonies, honors, and salutes -- United States; Pirates -- Mediterranean region; Naval officers